Pengaruh Kinerja Keuangan Terhadap Nilai Perusahaan Pada Perusahaan Manufaktur Di Bursa Efek Indonesia (Studi Empiris pada Perusahaan Manufaktur di Bursa Efek Indonesia Periode 2019-2021) - Shofia Alifa Hamidah; Dailibas Dailibas (Peneliti.net, 2022)
One independent variable, namely financial performance, is used in this study, as well as one dependent variable (firm value) and two moderating variables (and good corporate governance. The purpose of this research is to identify and analyze the effect of financial performance on firm value with dividend policy as a moderating variable.This study took a sample of 10 manufacturing companies listed on the Indonesia Stock Exchange for the period 2019 to 2020 using the purposive sampling method.The research hypothesis was tested using multiple analysis techniques and moderated regression analysis, with the SPSS (Statistical Product and Service Solutions The results of the study show that: 1) liquidity has no significant effect on firm value, 2) dividend policy is not able to significantly moderate the effect of liquidity on firm value, 3) leverage has no significant negative effect n on firm value, 4) dividend policy is not able to significantly moderate the effect of leverage on firm value, 5) Profitability has a significant positive effect on firm value, 6) dividend policy is not able to significantly moderate the effect of profitability on firm value.